2003
DOI: 10.1097/01.mlr.0000088301.06323.ca
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Volumes Associated With Higher Survival in Health Care

Abstract: There is evidence for a volume-mortality relationship for hospitals and physicians. The use of appropriate methods for analyzing additional diagnoses and interventions as well as a continuous systematic evaluation of the evidence is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 73 publications
0
74
0
4
Order By: Relevance
“…In 1979, Luft et al (1979) showed in their seminal paper that in ten out of twelve procedures a correlation between volume and outcome exists. Subsequent studies of this relationship predominantly confirmed this correlation (Gandjour et al, 2003;Halm et al, 2002). However, these studies inherently assume that volume is the driving factor for outcome (practice-makes-perfect hypothesis).…”
Section: Introductionmentioning
confidence: 77%
“…In 1979, Luft et al (1979) showed in their seminal paper that in ten out of twelve procedures a correlation between volume and outcome exists. Subsequent studies of this relationship predominantly confirmed this correlation (Gandjour et al, 2003;Halm et al, 2002). However, these studies inherently assume that volume is the driving factor for outcome (practice-makes-perfect hypothesis).…”
Section: Introductionmentioning
confidence: 77%
“…Over the last ten years, a large body of literature supporting the presence of a hospital volume-outcome relationship, including numerous systematic reviews, [18][19][20][21][22][23][24][25] has been developed. An early definitive systematic review on the subject was performed by Halm and colleagues and reported a significant association across a wide range of procedures and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Se debe tener en cuenta que dentro de un hospital puede haber variabilidad entre los cirujanos, en este estudio se decidió analizar la relación a nivel de hospitales, ya que: a) se acerca más al enfoque que es cambiar el sistema oncoló-gico a nivel de hospital; y b) además se debe tener en cuenta que en la literatura se describe que el volumen de pacientes atendidos por el hospital afecta más los resultados que el volumen de pacientes a nivel del cirujano (6).…”
Section: Métodosunclassified